A primer on weather and climate intervention for economists - Scott Knowles; Mark Skidmore (Center for Economic Studies and ifo Institute (CESifo), 2019)
There is limited public discourse and understanding about the history and science of weather and climate intervention, though scientists have researched, tested and implemented numerous methods of weather modification for six decades. Also, climate-related geoengineering is steadily gaining support as a means of combatting rising global temperatures. With climate change and associated increasing occurrence of extreme weather events, there has not been a more providential moment to consider the implications of anthropogenic, atmospheric intervention. This paper summarizes information about weather and climate intervention with the aim of answering the question: Why aren't more economists interested in evaluating weather and climate intervention activities?
Keywords: 330; weather modification; cloud seeding; geoengineering; climate change; economic analysis